2000
DOI: 10.1053/he.2000.5628
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of the CLIP score: A new prognostic system for patients with cirrhosis and hepatocellular carcinoma

Abstract: Prognosis of patients with cirrhosis and hepatocellular carcinoma (HCC) depends on both residual liver function and tumor extension. The CLIP score includes Child-Pugh stage, tumor morphology and extension, serum alfa-fetoprotein (AFP) levels, and portal vein thrombosis. We externally validated the CLIP score and compared its discriminatory ability and predictive power with that of the Okuda staging system in 196 patients with cirrhosis and HCC prospectively enrolled in a randomized trial. No significant assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(81 citation statements)
references
References 13 publications
1
79
1
Order By: Relevance
“…Various staging systems such as: (1) Okuda stage [56], (2) BCLC stage [1], (3) CLIP score, (4) JIS score [58,59 ](table 14), and (5) Tokyo Score [61], have all seen long-time use. The JIS score utilizing both the LCSGJ TNM and Child-Pugh stages is considered the most useful for overall staging of HCC in Japan [59,60].…”
Section: Staging For Hepatocellular Carcinomamentioning
confidence: 99%
“…Various staging systems such as: (1) Okuda stage [56], (2) BCLC stage [1], (3) CLIP score, (4) JIS score [58,59 ](table 14), and (5) Tokyo Score [61], have all seen long-time use. The JIS score utilizing both the LCSGJ TNM and Child-Pugh stages is considered the most useful for overall staging of HCC in Japan [59,60].…”
Section: Staging For Hepatocellular Carcinomamentioning
confidence: 99%
“…Various staging systems such as: (1) Okuda stage [27], (2) BCLC stage [28, 29], (3) CLIP score [30], (4) JIS score [31, 32] (table 8), and (5) Tokyo Score [33], have all been in long-time use. The JIS score utilizing both the LCSGJ TNM and Child-Pugh stages is considered the most useful for overall staging of HCC in Japan [31, 32].…”
Section: Staging For Hccmentioning
confidence: 99%
“…Notably, many studies validated the use of CLIP in HCC patients [6,7,8,9,10,11,12,13,14,15]. Furthermore, recent studies, including one of our patient population [5], evaluated the predictive accuracy of different HCC staging systems and showed that the CLIP score was more predictive than BCLC in the studied patient populations, which included a significant number of patients with advanced HCC [5,16,17].…”
Section: Introductionmentioning
confidence: 99%